2013
DOI: 10.3109/13880209.2012.761243
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivities and serum pharmacochemistry ofQi-Wei-Xiao-Yan-Tang

Abstract: Context: Qi-Wei-Xiao-Yan-Tang (XYT), composed of Radix et Rhizoma Rhei, Radix Astragali, Radix Wikstroemiae Indicae, Fructus Ligustri Lucidi, Poria and Radix Glycyrrhizae, has been widely used as an anti-inflammatory drug.Objective: The present study investigated the anti-inflammatory, antibacterial effects and serum pharmacochemistry of XYT. Methods: The dimethylbenzene-induced inflammation test, the acetic acid-induced vascular permeability test and the carrageenan-induced paw edema test were used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 26 publications
(21 reference statements)
2
15
0
Order By: Relevance
“…HWTX is an anti-bacterial agent which is also known to purge heat and flatulence from the bowels. Previous studies showed that the herbal components of HWTX possess significant beneficial effects against inflammatory reactions and gastrointestinal dysfunction [12,17,18]. In the present investigation, the results obtained indicate that HWTX in combination with standard AP treatment significantly improved AP syndromes when compared with control patients.…”
Section: Discussionsupporting
confidence: 71%
“…HWTX is an anti-bacterial agent which is also known to purge heat and flatulence from the bowels. Previous studies showed that the herbal components of HWTX possess significant beneficial effects against inflammatory reactions and gastrointestinal dysfunction [12,17,18]. In the present investigation, the results obtained indicate that HWTX in combination with standard AP treatment significantly improved AP syndromes when compared with control patients.…”
Section: Discussionsupporting
confidence: 71%
“…The xylene-induced ear edema in mice is a preliminary and simple model for screening potential antiinflammatory drugs [10]. The results of xylene-induced ear edema showed that GL had a significant anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…), and vehicle+GL (160 mg/kg, i.p.). Xylene-induced ear edema in mice was initiated according to a method previously described by He et al [10]. Briefly, each group was pre-treated with the drugs.…”
Section: Xylene-induced Ear Edema Testmentioning
confidence: 99%
“…Dimethylbenzene-induced ear edema in mice, produced as described by He et al [20], was used to evaluate the anti-inflammatory activity of MEAP. Briefly, MEAP was administered orally 1 h before dimethylbenzene topical application to the right ear.…”
Section: Methodsmentioning
confidence: 99%